Modulation of bone marrow mesenchymal stem cell secretome by ECM-like hydrogels - Silva, N. A. (2013)
It has been demonstrated that bone marrow mesenchymal stem cell (BM-MSCs) transplantation has beneficial effects on several central nervous system (CNS) debilitating conditions. Growing evidence indicate that trophic factors secreted by these cells are the key mechanism by which they are acting. These cells are frequently used in combination with 3D artificial matrices, for instance hydrogels, in tissue engineering-based approaches. However, so far, no study has been reported on the influence of such matrices, namely the presence or absence of extracellular matrix motifs, on BM-MSCs secretome and its effects in neuronal cell populations. In this sense, we herein studied the impact of a hydrogel, gellan gum, on the behavior and secretome of BM-MSCs, both in its commercial available form (commonly used in tissue engineering) and in a fibronectin peptide-modified form. The results showed that in the presence of a peptide in the gellan gum hydrogel, BM-MSCs presented higher proliferation and metabolic activity than in the regular hydrogel. Moreover, the typical spindle shape morphology of BM-MSCs was only observed in the modified hydrogel. The effects of the secretome of BM-MSCs were also affected by the chemical nature of the extracellular matrix. BM-MSCs cultured in the modified hydrogel were able to secrete factors that induced higher metabolic viabilities and neuronal cell densities, when compared to those of the unmodified hydrogel. Thus adding a peptide sequence to the gellan gum had a significant effect on the morphology, activity, proliferation and secretome of BM-MSCs. These results highlight the importance of mimicking the extracellular matrix when BM-MSCs are cultured in hydrogels for CNS applications.